Phytochemical Screening and Antidiabetic, Antihyperlipidemic, and Antioxidant Effects of Leptopus Cordifolius Decne. In Diabetic Mice - Rahman, Shahid; Jan, Gul; Jan, Farzana Gul; Rahim, Hafeez Ur (Frontiers in Pharmacology, 2021)
Plants are well known in traditional herbal medicines for their hypoglycemic and hypolipidemic activities due to their accessibility, affordability, and corollary effects. Leptopus cordifolius has been reported to control diabetes in folkloric medicine, but no known scientific research has been conducted to assess the plausibility of this assertion. Therefore, the current study is aimed to investigate the antidiabetic and hypolipidemic effects of Leptopus cordifolius leaves in alloxan-induced diabetic mice. The antidiabetic and antihyperlipidemic evaluation was conducted in Swiss albino mice at the dose of 150-250 mg/kg for 15 days. The blood glucose, total cholesterol, triglyceride, LDL, HDL, creatinine, ALP, SGPT, and SGOT level were estimated according to standard procedures. Phytochemicals of leaves were analyzed using GC-MS analysis. Enzymatic antioxidant activity of the plant was investigated spectrophotometrically by carrying out superoxide dismutase, peroxidase, and catalase assays. The membrane stabilization potential of L. cordifolius leaves extracts was carried out using an in vitro haemolytic assay. The results revealed that a dose response effect with the methanolic extract of L. cordifolius which had significant antihyperglycemic effects at 150-250 mg/kg in alloxan treated mice, although less than the positive control (glibenclamide). Hyperlipidemic activity was significant at 250 mg/kg. The biochemical parameters such as total cholesterol, triglyceride, LDL, HDL, creatinine, ALP, SGPT, and SGOT were significantly improved (p<0.01) by the methanolic extract of 250 mg/kg compared to the diabetic group. Treatment for 15 days showed significant elevation (p<0.01) of antioxidant enzymes. GC-MS analysis provided tentative identifications of 52 compounds in the methanolic extract of L. cordifolius of which 12 compounds have reported antidiabetic activity. In conclusion methanolic extract of L. cordifolius of 150 and 250 mg/kg body weight showed significant antidiabetic and antihyperlipidemic activities in alloxan-induced diabetic mice and with further work, has the potential to be used to manage blood glucose and cholesterol levels.